2003
DOI: 10.1007/s10038-003-0105-4
|View full text |Cite
|
Sign up to set email alerts
|

Common single nucleotide polymorphisms of the MDR1 gene have no influence on its mRNA expression level of normal kidney cortex and renal cell carcinoma in Japanese nephrectomized patients

Abstract: In this study, we have quantified the mRNA expression levels of multidrug resistance gene 1 (MDR1) in the normal kidney cortex and renal cell carcinoma (RCC) segments from 24 Japanese nephrectomized patients by real-time polymerase chain reaction (PCR). The mRNA expression level of MDR1 in RCC segments was significantly decreased in comparison with each normal segment (P=0.0042, by StudentÕs paired t-test). In addition, the ten common single nucleotide polymorphisms (SNPs) of the MDR1 gene in the patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
(27 reference statements)
1
25
0
Order By: Relevance
“…24,25 We also believe that including intronic SNPs 7 and 8 and haplotypes defined by these two SNPs in analysis of P-gp functional expression might help to better understand the functional consequences of MDR1 polymorphisms. Uwai et al 26 suggested intron 16 poly- MDR1 polymorphisms in Crohn disease and ulcerative colitis U PotoWnik et al 535 morphism (SNP8 in our study)-dependent downregulation of P-gp expression in the kidney cortex during tumor development. However, the expression and functional data to date are mainly available for coding SNPs in exons 21 and 26.…”
Section: Discussionsupporting
confidence: 50%
“…24,25 We also believe that including intronic SNPs 7 and 8 and haplotypes defined by these two SNPs in analysis of P-gp functional expression might help to better understand the functional consequences of MDR1 polymorphisms. Uwai et al 26 suggested intron 16 poly- MDR1 polymorphisms in Crohn disease and ulcerative colitis U PotoWnik et al 535 morphism (SNP8 in our study)-dependent downregulation of P-gp expression in the kidney cortex during tumor development. However, the expression and functional data to date are mainly available for coding SNPs in exons 21 and 26.…”
Section: Discussionsupporting
confidence: 50%
“…11,12 Very recently, it was shown that the 3435C4T polymorphism may influence mRNA stability. 13 The influence of ABCB1 polymorphisms on expression and function in kidney tissue was examined in a Japanese sample, showing no influence on mRNA expression in normal kidney cortex as well as in renal cell carcinoma (RCC) tissue, 14 whereas in a German sample, a strong association of ABCB1 3435C4T to the risk of non-clear-cell renal cell carcinoma (non-CCRCC) was described. 15 To our knowledge, there is no data available on the significance of ABCC2 variants to MRP2 expression or function in normal renal tissue or in renal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…18 Two studies have described the opposite association, that is, the T polymorphism associated with increased mRNA expression, but once again these have been either nonsignificant 19 or performed on a very small sample. 20 The majority have failed to find an association, 17,[21][22][23][24][25] although two of these negative studies did show an association with haplotype rather than genotype. 17,21 Most studies of the 2677G4TA polymorphism and mRNA expression levels have also been negative, 17,19,21,[23][24][25] although one study 22 did report an association between the GG2677 genotype and reduced mRNA expression.…”
Section: Effects Of Genotype On Abcb1 Mrna and Protein Expressionmentioning
confidence: 99%
“…Associations with other polymorphisms in the ABCB1 gene have been equally inconclusive. The majority of studies have failed to show a significant association between 2677G4TA and mRNA expression 17,19,21,[23][24][25] or with PGP expression. 17,23,24,26,27 Other ABCB1 polymorphisms have similarly also failed to demonstrate positive associations.…”
Section: Gd Leschziner Et Almentioning
confidence: 99%